Utility and safety of airway stenting in airway stenosis after lung transplant: A systematic review - Wang, Zilin; Zhao, Bo; Deng, Mingming; Tong, Run; Bian, Yiding; Zhang, Qin; Hou, Gang (Frontiers in Medicine, 2023)
Background: Airway complications seriously affect the clinical outcomes and long-term prognosis of lung-transplantation patients. Airway stenting provides effective palliation for patients with airway stenosis. However, a lack of consensus regarding the efficacy and safety of airway stents in airway stenosis after lung transplantation. This study critically evaluated all available evidence regarding this concern. Methods: We retrieved studies from EMBASE, PubMed, and Cochrane Library databases. Studies were included if they reported baseline characteristics of airway complications after lung transplantation, stenting for airway stenosis, or prognosis. Results: In total, 279 papers were screened and 17 papers were included in final analysis. The short-term efficacy of airway stenting was assessed in almost all studies, with immediate palliation in symptom and improved pulmonary function reported. Eleven of the included studies evaluated the long-term efficacy of stent therapy, with no obvious improvement in the survival rate. Stent-related complications are common regardless of the material; However, serious complications are rare and can be improved with routine management. Conclusion: We demonstrated that airway stenting is a safe and effective method to treat airway stenosis after lung transplantation. The short-term effect is significant, while the long-term efficacy is not distinct and sustainable.